Avaliação dos parâmetros inflamatórios em asininos (equus asinus africanus) submetidos a orquiectomia - Rodrigues, Luan Aragão (Universidade Federal Rural do Semi-Árido, 2019)
The aim of this study was to evaluate the inflammatory parameters in donkeys (Equus asinus africanus) submitted to closed orchiectomy technique by scrotal access and a new approach (paraescrotal). Twelve donkeys were divided into two groups: group 1 (GI) performed the orchiectomy technique through the para-scrotal surgical access and group 2 (GII) performed the orchiectomy technique using the scrotal access (conventional). Postoperative evaluations consisted of macroscopic evaluation of the surgical wound, hematological parameters and peritoneal fluid, which occurred in both groups at moments (M): M0 (before the surgical procedure), and the other moments after surgery, M12 ( twelve hours), M24 (twenty four hours), M48 (forty eight hours), M72 (seventy two hours), M8D (eight days) and M16D (sixteen days). Surgical wounds were evaluated according to bleeding and scrotal edema intensity. Hematological, physicochemical and biochemical examinations of the peritoneal fluid were performed. The techniques used did not generate an important systemic inflammatory response to the point of detection by leukogram and fibrinogen dosage. In peritoneal fluid no differences were observed between groups. A para-scrotal technical proposal requires longer surgery, but promotes less bleeding, less edema and faster healing.
Keywords: Inflamação; Jumentos; Líquido peritoneal; Abordagem cirúrgica; Castração; Inflammation; Donkeys; Peritoneal fluid; Surgical approach; Castration; CIENCIAS AGRARIAS::MEDICINA VETERINARIA